Adaptation To Changes In The Fishing Season At The Village And Subdistrict Posek Posek Islands Regency Lingga Riau Islands Province. - Irak Irak; Kusai Kusai; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrakThis study aims to analyze the Adaptation of Fishermen Against Change of Season In Posek Village, Posek Islands, Ligga Regency, Kepulauan Riau Province. Respondents in this research are fishermen community who have fishing gear and fishing equipment Bubu in Posek Village, Posek District, Lingga Regency, Riau Islands Province with main informant as many as 12 people. Data collection techniques used were surveys and interviews.The results of this research show that the fisherman Village Posek keep doing activities on the ocean at the time of the seasons change though not routine. And the activity being performed based on capture tool which is used by fishermen Village Posek. The activity carried out by fishermen to meet the needs of everyday family despite changing weather conditions at the time of the turn of the seasons and the seasons causing certain conditions area of the catchment is not very good even harmful. Load a dependent family and caused most of the fishermen have to keep doing activities on the ocean even though the weather was not good or looking for another job if it couldn't sail or conduct arrest this research also shows that the behavior the adaptation was done by the fisherman Village Posek by changing the capture tool, change the area of arrest and at the moment weather conditions cause they can't conduct arrests. The activity at the time of arrest is not doing that is looking for another job like being a construction worker, managing the estate, repairing the ship, captured near the beach and looking for work in other areas but some are just waiting for the. Keywords: Adaptation, Change of Season, Fisherman